Finland: Decentralisation tendencies within a collective wage bargaining system - Rita Asplund (The Research Institute of the Finnish Economy (ETLA), 2007)
This paper provides a brief overview of the Finnish wage bargaining system and its evolution over the past decades into its current mode by drawing on existing documents, reports and analyses. The emphasis is on the changes having occurred in the system's overall structure as well as in its main content. Finally attempts are made, by use of the existing empirical evidence, to contrast these changes against the development of wages and the unionisation rate. The paper concludes with a brief discussion of future challenges as expressed in recent studies of the Finnish wage bargaining system.
Keywords: J52; 330; collective agreement; Finland; wage bargaining; Lohnverhandlungen; Tarifvertrag; Wirtschaftsgeschichte; Finnland